Insights Into Host Cell Cytokines in Chlamydia Infection - Xiang, Wenjing; Yu, Nanyan; Lei, Aihua; Li, Xiaofang; Tan, Shui; Huang, Lijun; Zhou, Zhou (Frontiers in Immunology, 2021)
Chlamydial infection causes a number of clinically relevant diseases and induces significant morbidity in humans. Immune and inflammatory responses contribute to both the clearance of Chlamydia infection and pathology in host tissues. Chlamydia infection stimulates host cells to produce a large number of cytokines that trigger and regulate host immune responses against Chlamydia. However, inappropriate responses can occur with excessive production of cytokines, resulting in overreactive inflammatory responses and alterations in host or Chlamydia metabolism. As a result, Chlamydia persists and causes wound healing delays, leading to more severe tissue damage and triggering long-lasting fibrotic sequelae. Here, we summarize the roles of cytokines in Chlamydia infection and pathogenesis, thus advancing our understanding chlamydial infection biology and the pathogenic mechanisms involved.